2019
DOI: 10.1249/mss.0000000000002151
|View full text |Cite
|
Sign up to set email alerts
|

“Chemotherapy-periodized” Exercise to Accommodate for Cyclical Variation in Fatigue

Abstract: Purpose The purpose of this study was to provide a rationale for “chemotherapy-periodized” exercise by characterizing cyclical variations in fatigue and exercise response across a chemotherapy cycle and comparing exercise adherence during chemotherapy between a prescription that is periodized according to chemotherapy cycle length and a standard linearly progressed prescription. Methods Women with breast cancer who were prescribed taxane-based chemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 19 publications
5
30
0
Order By: Relevance
“…A study which characterized cyclical variations in fatigue across a taxane-based chemotherapy cycle showed that fatigue increased from baseline to prior to the third treatment, then peaked at 3-5 days after the third treatment, before recovering prior to the next treatment. 22 Our result was similar to this, through VAS-F, we can see that the scores of VAS-F were climbing at the time of starting the third cycle chemotherapy in sham and nonacupuncture groups.…”
Section: Dovepresssupporting
confidence: 89%
“…A study which characterized cyclical variations in fatigue across a taxane-based chemotherapy cycle showed that fatigue increased from baseline to prior to the third treatment, then peaked at 3-5 days after the third treatment, before recovering prior to the next treatment. 22 Our result was similar to this, through VAS-F, we can see that the scores of VAS-F were climbing at the time of starting the third cycle chemotherapy in sham and nonacupuncture groups.…”
Section: Dovepresssupporting
confidence: 89%
“…The difficulty of attending the gym may be explained by cancer-related barriers (e.g., disease and treatment-related symptoms, and medical appointments), which have been previously described as the main reason for lower attendance during treatment. 27 , 31 , 35 , 36 Thus, our findings reflect the need to overcome such barriers where possible. A periodized exercise prescription with adjustments for such cancer-related barriers (e.g., an adapted progressive overload and recovery depending on treatment phase) could be appropriate.…”
Section: Discussionmentioning
confidence: 56%
“…For supervised group-based resistance training, exercise adherence was within the range reported in other exercise interventions involving patient undergoing curative cancer treatment. 27 , 31 - 34 However, comparisons are limited due to the lack of studies reporting adherence according to all FITT-principles and the difference in calculation methods. 16 , 24 - 26 Overall adherence and attendance were lower than adherence in terms of intensity, time and type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, not all frequency schedules will likely be feasible for a specific exercise intensity (e.g. daily exercise at high intensity) and carefully considered periodisation schedules will need to be employed to maintain exercise tolerability during treatment [44,82].…”
Section: Implications For Future Researchmentioning
confidence: 99%